JENIS DAN MANFAAT TUMBUHAN PESISIR PASIR JAMBAK, KELURAHAN PASIR NAN TIGO, KECAMATAN KOTO TANGAH, KOTA PADANG - Nurul Fathya; Reki Kardiman; Filza Yulina Ade (Jurnal Biogenerasi, 2026)
Coastal areas are ecosystems that have diverse plants with potential uses for local communities. This utilization is important to document as a basis for managing biological resources and preserving ethnobotanical knowledge based on local wisdom. This study aims to identify coastal plant species and analyze their utilization by the community in the Pasir Jambak Beach area, Padang City. This study used a descriptive method through field observations, specimen collection, and semi-structured interviews. The results showed that there were 26 plant species from 18 families utilized by the Pasir Jambak community. These species consist of 13 tree habitus, 10 shrubs, 3 herbs, and 1 palm group. Plant utilization is dominated as traditional medicine and food ingredients. The plant with the highest utilization value (Use Value) is coconut (Cocos nucifera) at 0.1 and the species with the lowest UV value is Dendrocnide stimulans with a UV value of zero. These results indicate that coastal plants have important potential in supporting community life and need to be preserved sustainably